2020
DOI: 10.3390/f12010039
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization and Tree Species Influence on Stable Aggregates in Forest Soil

Abstract: Background and objectives: aggregation and structure play key roles in the water-holding capacity and stability of soils and are important for the physical protection and storage of soil carbon (C). Forest soils are an important sink of ecosystem C, though the capacity to store C may be disrupted by the elevated atmospheric deposition of nitrogen (N) and sulfur (S) compounds by dispersion of soil aggregates via acidification or altered microbial activity. Furthermore, dominant tree species and the lability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Estimation of soils resistance to erosion is referred to as 'erodability' of soil, based on its physical characteristics (Kemner and Adams, 2021). Primary factors affecting erodability are soil texture, organic matter content, structure and permeability.…”
Section: Background and Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…Estimation of soils resistance to erosion is referred to as 'erodability' of soil, based on its physical characteristics (Kemner and Adams, 2021). Primary factors affecting erodability are soil texture, organic matter content, structure and permeability.…”
Section: Background and Contextmentioning
confidence: 99%
“…Primary factors affecting erodability are soil texture, organic matter content, structure and permeability. Greater infiltration, organic matter and structure improve soils resistance to erosion (Kemner and Adams, 2021, Lawaal, 2009, Lal, 2015.…”
Section: Background and Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated the effects of fertilization on biomass growth during forest restoration with leguminous trees [21,22]. Fertilization effects may enhance the drought tolerance of species due to increased quantum yield [23,24]. A few studies have evaluated the combined effects of seasonality and fertilization on chlorophyll fluorescence.…”
Section: Introductionmentioning
confidence: 99%